2011
DOI: 10.1007/s11030-011-9327-0
|View full text |Cite
|
Sign up to set email alerts
|

A facile and one pot synthesis of 1,4-disubstituted-1H-1,2,3-triazoles from terminal alkynes and phenacyl azides prepared from styrenes by CAN oxidant and sodium azide

Abstract: A facile and green synthesis of 1,4-disubstituted-1H-1,2,3-triazoles is reported. The reaction of α-azido ketones and terminal alkynes in the presence of [CuSO(4) (H(2)O)(5)/sodium ascorbate] in a mixture of H(2)O/polyethylene glycol 400 as solvent afforded the corresponding 1,4-disubstituted triazoles at ambient temperature with short reaction times and at high yields. The corresponding α-azido ketones were directly prepared in situ from various substituted styrenes using the oxidant cerium ammonium nitrate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 24 publications
1
7
3
Order By: Relevance
“…21 Previously, it was shown that "click" synthesis of 1,4-disubstituted 1,2,3-triazoles proceeded in good yields using CuSO 4 + NaAsc in PEG 400/water under mild conditions for a short time, due to very efficient activation by PEG 400. [22][23][24][25] However this effect is not observed in the present study, because similar yields were obtained when compared between A and B under different catalysts loading. It appears that the concentration of PEG played a key role in the previous studies (PEG 400/water = 1:1, v:v).…”
Section: Introductioncontrasting
confidence: 58%
See 1 more Smart Citation
“…21 Previously, it was shown that "click" synthesis of 1,4-disubstituted 1,2,3-triazoles proceeded in good yields using CuSO 4 + NaAsc in PEG 400/water under mild conditions for a short time, due to very efficient activation by PEG 400. [22][23][24][25] However this effect is not observed in the present study, because similar yields were obtained when compared between A and B under different catalysts loading. It appears that the concentration of PEG played a key role in the previous studies (PEG 400/water = 1:1, v:v).…”
Section: Introductioncontrasting
confidence: 58%
“…It appears that the concentration of PEG played a key role in the previous studies (PEG 400/water = 1:1, v:v). [22][23][24][25] Here the present PEG concentration is too low to provide such an effect, and therefore the PEG ligand does not lead to a good yield. When the monofunctional 1,2,3-triazole terminated with PEG 2000 (PEG-mono-trz-Cu I , 1 equiv., C), 26 was introduced the yields increased, especially that under low catalyst amounts (i.e.…”
Section: Introductionmentioning
confidence: 88%
“…The solid products were easily recrystallized from a mixture of ethanol/water (1:3 v/v) or in some cases from ethanol (Table 1, entry 13 and 14). Click condensations were confirmed by the appearance of a singlet in the region of 8–8.5 ppm in 1 H-NMR spectra, which corresponds to the hydrogen on 5-position of triazole ring and confirms the regioselective synthesis of 1,4-disubstituted triazole regioisomers (Keshavarz and Badri 2011). …”
Section: Resultsmentioning
confidence: 56%
“…Finally the solid residue was re-crystallized from EtOH/H 2 O (3:1 v/v) to afford the product. All obtained triazoles (7a-k) were known and their physical data were compared with those of authentic compounds and found to be identical [24][25][26][27][28][29][30][31][32][33][34][35][36]. 2.5.…”
Section: Syntheses Of 14-disubstituted Triazoles: a Typical Proceduresmentioning
confidence: 99%
“…Due to our interests in heterogeneous catalysis, applied in a variety of organic transformations [13][14][15][16][17][18][19][20][21][22][23], and recent successful attempts for the syntheses of 1,2,3-triazoles, via click reaction [24][25][26][27][28][29][30][31][32][33][34][35][36], in this paper we wish to report the preparation of copper nano catalyst on modified KIT-5 (CuI/AK) as a superior heterogeneous catalyst in the syntheses of 1,2,3-triazoles via click reaction. This heterogeneous catalyst system exhibited an excellent catalytic performance for 1,3-dipolar Huisgen cycloaddition reaction in the construction of the various 1,2,3-triazole derivatives.…”
Section: Introductionmentioning
confidence: 99%